The Search for Mind-Body Flourishing in Spinoza's Eudaimonism - Smith, Brandon, (New Research in the History of Western Philosophy ;, 2026)
The Search for Mind-Body Flourishing in Spinoza's Eudaimonism explores the ethical tradition of eudaimonism, which considers happiness or flourishing as (a) partly objective or naturalistic, (b) partly subjective or affective, (c) structurally stable, and (d) the highest good. It examines the insights of Aristotle, Epicurus, the Stoics, and Spinoza concerning the respective roles of pleasure, virtue, and mind and body in living an eudaimonistically happy life. Spinoza offers an especially rich account of happiness, in opposition to the intellectualism of his fellow eudaimonists, through his argument for non-reductive mind-body identity, which entails that flourishing is equally intellectual and physical in nature.